A Pragmatics Analysis of Positive Politeness Strategies on Nwal Hadaki Speech in TED TALKS - Aulia Febriani; Aidil Syah Putra; Fauzan Rofiqi (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2024)
Every individual aims to convey their ideas in a polite manner to positively impact their audience. The effective use of positive politeness strategies is crucial in speech, as it helps to create a positive and engaging interaction with the audience. The one of the fascinating objects to be analyzed in terms of positive politeness strategies is the speech on TED Talk video by Nwal Hadaki entitled “How Long it Takes to Change Your Life?”. This research aims at discovering and analyzing the positive politeness strategies in the speech on TED Talk video by Nwal Hadaki entitled “How Long it Takes to Change Your Life?”. The method used in this study is descriptive qualitative research. The data consisted of statements and sentences spoken by Nwal Hadaki. The primary tool used to collect the data was a data sheet. The data were analyzed using a referential method, which examines the data in relation to the theoretical framework employed in this study. The findings indicate that all 15 positive politeness strategies were present, The most frequently used strategies are: Intensifying the listener's interest in the speaker's contribution (3 occurrences) and Seeking agreement on safe topics (3 occurrences). The second most common strategies include: Exaggerating interest, approval, or sympathy, Being optimistic that the listener wants what the speaker wants, and Giving or asking for reasons. The third most common strategies are: Avoiding disagreement, Joking to put the hearer at ease (each occurring once), These strategies demonstrate Nwal Hadaki's use of positive politeness to engage and persuade the audience effectively.